Modern Treatment Methods for Acnes. - Kholmatov Murodjon Sobirovich; Sharipov Alisher Urmanovich; Kamalov Azizbek Ruzalievich; Begmatov Islombek G'anievich. (Academia One Publishing, 2025)
Acne, a common dermatological condition, affects individuals of all ages, causing physical and psychological distress. This article explores modern treatment methods, analyzing their effectiveness and potential side effects. It provides insights from contemporary literature and outlines innovative approaches in dermatology to address acne
Keywords: Acne treatment; dermatology